2020
DOI: 10.21009/004.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Education Learning Approaches in Shaping Students’ Emotional Intelligence in the Digital Age

Abstract: Over the last several decades have witnessed nothing short of a transformation in the study of religion. The human race lives in a time of deep concern for the future of the biosphere. Globalization can bring a paradox to the practice of Islamic education. Islamic education has a significant role in shaping the ethics and morals in the life of the people and of the nation to create religious and devoted people. The objective of this study was to describe the Islamic education learning approaches discourse stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 7 publications
0
30
0
10
Order By: Relevance
“…The drawback of the learning technology breakthrough is indicated in terms of difficulty of use, because not all students have access to a representative media for applying technology-based learning (online) [60]. In [61], strategic planning including innovative and digital learning is encouraged in Islamic education. We argue that technology has also contributed to the people that are not used to it.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of the learning technology breakthrough is indicated in terms of difficulty of use, because not all students have access to a representative media for applying technology-based learning (online) [60]. In [61], strategic planning including innovative and digital learning is encouraged in Islamic education. We argue that technology has also contributed to the people that are not used to it.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…According to the findings of the study by [60], the efficacy of this learning technology advancement increases students' comprehension of the subject matter, because content from teaching materials is discovered and exercised by the students themselves. The results of the qualitative study by [61] revealed that the development of active learning methods through good strategic planning can shape the students' emotional intelligence for Islamic education.…”
Section: (Rq2) What Practices Of Information Technology Are Adopted For Learning Islamic Education?mentioning
confidence: 99%
“…Pembelajaran kurikulum 2013 guru dituntut dapat memberikan kegiatan belajar aktif dan berpusat pada siswa (Tohir, 2019 (Mansir & Karim, 2020).…”
Section: Pendahuluanunclassified
“…Education is an essential thing in human life, . Speaking of globalization in the world of education, this is certainly a challenge and hope for educators because automatically the requirement to increase the quality standard of education will be even higher (Mansir & Karim, 2020).…”
Section: Introductionmentioning
confidence: 99%